From “Unbelievable Stupidity” to “Secret Clues for Staying Healthy”: CAM Landscape and Boundary-Work in Estonian and Finnish Mainstream Media in April 2020 - Hiiemäe Reet; Utriainen Terhi (ESTONIAN LITERARY MUSEUM, 2022)
Based on a one-month (April 2020) comparative observation of media content in three Estonian and three Finnish mainstream media sources (two daily newspapers and one weekly women's magazine) along with some examples from an earlier period, the authors analysed the representation of complementary and alternative medicine (CAM) in the media. The analysis showed that the media from the two countries presented CAM both in its various mainstream and more fringe forms, and that pejorative as well as complimentary and attracting undertones were present. The authors conclude that CAM topics were present in the selection of sources as methods for wellbeing and healing but also as entertaining, exoticising, warning, and mystical-metaphorical allusions along with different levels of boundary-work, especially science. The authors also noted interesting differences between the chosen media both within one country and between the two countries in terms of how much CAM was present as well as in which ways it was treated. In the Estonian material, the scale of tones was broader: the texts presented highly sensational, exoticising and othering angles towards approaches that were considered extreme and dangerous but mainly entertainment-oriented, and they positively described healing and wellbeing practices, sometimes with a mystic touch. The Finnish media was more low-key in its representations and tone: the mentions were shorter and less frequent. Although the Finnish material had more positive representations, this does not suggest that CAM is more tolerated in Finland - the Finnish media presented less extreme forms of CAM, which gave less ground for journalistic opposition.